Literature Review: Pengalaman Perawat dalam Melakukan Resusitasi Jantung Paru - Yoany Maria V.B. Aty; Ignatius Tanesib; Rohana Mochsen (Bima Nursing Journal, 2021)
Background : Sudden death is still the main cause of death. WHO explains that most sudden deaths are caused by heart attacks. The role of nurses to prevent the death rate of cardiac arrest patients, the ability to perform cardiopulmonary resuscitation. Objective: This study aims to determine the experience of nurses in performing cardiopulmonary resuscitation. Methods: This research is a literature study by conducting a review of previous research using some relevant literature. Search articles using several search engines, including Google, Google Scholar, Research Gate, and emergency nursing journal, PUBMED journal, SINTA with the limitation of the journal publication year for the last 10 years, starting from 2011-2020. Articles used in Indonesian and English are downloaded in full text in PDF format and are free articles. Results: Based on the analysis of relevant journals, it was found that the experience of nurses in performing cardiopulmonary resuscitation is very important in efforts to save patients with cardiac and pulmonary arrest problems. Conclusion: The experience of nurses doing resuscitation is very important in an effort to save patients with respiratory and cardiac arrest problems. The experience of nurses needs to be improved through training so that nurses have the knowledge and skills to carry out resuscitation.